Progress of isolation, chemical synthesis and biological activities of natural chalcones bearing 2-hydroxy-3-methyl-3-butenyl group - Zhai, Jiadai; Sun, Bingxia; Sang, Feng (Frontiers in Chemistry, 2022)
Chalcones have a three-carbon α,β-unsaturated carbonyl system composed of two phenolic rings. Many chalcones have shown broad spectrum of biological activities with clinical potentials against various diseases. They are usually abundant in seeds, fruit skin, bark and flowers of most edible plants. Among them, chalcones bearing 2-hydroxy-3-methyl-3-butenyl (HMB) group have been reported several times in the past few decades due to their novel scaffolds and numerous interesting biological activities. In this paper, we reviewed the isolation of twelve natural chalcones and a natural chalcone-type compound bearing 2-hydroxy-3-methyl-3-butenyl group discovered so far, and reviewed their synthesis methods and biological activities reported in the literature. We anticipate that this review will inspire further research of natural chalcones.